PENGGUNAAN MODEL PEMBELAJARAN DISCOVERY LEARNING MELALUI MEDIA WORD SQUARE UNTUK MENINGKATKAN KEAKTIFAN DAN KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN LARUTAN ELETROLIT DAN NON ELEKTROLIT DAN KOLOID DI KELAS X KIMIA ANALIS SMKN 2 PEKANBARU - Lidiana Fitri; Nofianti Nofianti (Jurnal Pendidikan Kimia Universitas Riau, 2019)
This research study about application of discovery learning model through word square media to increase activity and student mastery learning. This research goal to know whether discovery learning model through word square media can increase activity and student mastery learning and whether this model were pleased by student. This research is class action research consisted of 2 cycle, where first cycle is electrolyte and non-electrolyte solutions chapter and second cycle is colloid. This research done in SMKN 2 Pekanbaru at X Kimia Analis class in year 2016/2017. In this research, data collected with teacher and student observation sheet, LKS and evaluation value, block test value and student perception enquette in lerning as supporter data. As for result obtained for the student activity, clasical student mastery learning according to national and school standard in first cycle average are 53, 40%, 96,97% and 93,94% and also for second cycle are 65,36%, 100% and 93,94%. Student perception to study discovery learning through word square media applied get positive respon, this matter can see from student percentage amount chosening very agree and agree for the first cycle and second cycle enquette answer successively are 91,73% and 93,47%.